Sequence diagram synthesis theory for stitching together multiple sequence diagrams through formal semantics modelling - Ameedeen, Mohamed Ariff; Zamli, K. Z.; Ong, Muhamad Idaham Umar; Thong, Weng Jie
The aim for this thesis is to bridge the gap between Sequence Diagram, Petri Nets and SD2PN. Sequence Diagram is a behavioral type of UML diagram widely used by software developers to show dynamic interactions in a system, while Petri Net is a modelling language that is able to carry out mathematical analysis for a system that is also capable of expressing dynamic interaction in a system. SD2PN is a tool that enables software developers to map Sequence Diagram to Petri Nets. Software developers are able to map Sequence Diagram to Petri Nets and perform mathematical analysis using Petri Net tools to check for any error before the actual coding phase. This will in turn result in less error during the coding phase. However, SD2PN only supports one way mapping, which is from Sequence Diagram to Petri Nets. Users have to manually update the Sequence Diagram if any error is to be found when analyzing the Petri Nets. This thesis aims to find a way to map Petri Nets back to Sequence Diagram, so that software developers are able to map the Petri Nets back to Sequence Diagram instead of updating the Sequence Diagram manually. This is the main motivation for this thesis, which is to create an algorithm for mapping Petri Nets to UML Sequence Diagram. This thesis is also been done to fulfill the requirement of my masters study.